THE PETS:Game Introduction of Pets in Two Languages - Wahyu Febriyanto; Brenda Chandrawati; Erdhi Widyarto (Soegijapranata Catholic University, 2016)
Introducing environment is important for children. Included in this environment is the life of living beings such as humans, animals, and plants. The role of parents is needed in introducing the living creatures. One of the living creatures that endeared children are animals, especially the pets. Therefore made educational game The Pets. With the game